Determination of Research Bias Based on the Articles Published in Health Management Journals - Sahar Amouzade; Zahra Aghalari; Aram Tirgar (Mazandaran University of Medical Sciences, 2017)
Introduction and purpose: Content analysis of scientific articles conducted in the field of Health Systems Management through identifying the priorities and outcomes can help authorities in decision-making. The present study aimed to determine the status of research bias in the articles published in  scientific journals in the field of Health Systems Management. Methods: In this cross-sectional study, 659 articles from 87 issues of 4 scientific journals in the field of Health Systems Management (from the first year of publishing through the end of 2014) were surveyed using the census method. A researcher-made checklist was used for data collection, and descriptive statistics were utilized for data analysis. Results: From different research areas, the highest percentage of published papers (23.4%) were on Health Systems Management and 18.4% belonged to the Human Resources Management. In 27.3% and 13.3% of the surveyed papers, the study populations were limited to staff and managers, respectively. More than two thirds of the papers (89.3%) were derived from original articles, 59.4% of them were descriptive studies, and over half of the papers were questionnaire-based. Conclusion: Despite the wide variety of subjects in Health Systems Management articles, some areas such as physical management and medical equipment and supplies have been neglected. Thus, a balanced subject distribution along with an emphasis on novel and practical studies is recommended.